Detection of the "Crossed Aorta Sign" during Echocardiography before Angiography. (14th December 2017) - Massobrio, Laura; Valbusa, Alberto; Bertero, Giovanni; Montecucco, Fabrizio; Rosa, Gian Marco; Bezante, Gian Paolo; Brunelli, Claudio
Abstract : We report the case of an anomalous circumflex (Cx) origin from the right sinus of Valsalva with retroaortic course observed in a modified apical four-chamber view during transthoracic study (TTE). This finding is known as the "crossed aorta sign." Usually, the diagnosis of this congenital anomaly of coronary circulation is established during coronary angiography. In this case, the diagnosis was performed by echocardiography before angiography. We believe that recent improvements in echocardiography increase the potential of this imaging technology also in the diagnosis of coronary artery anomalies.